Neogene and early Pleistocene flora from Alaska, USA and Arctic/Subarctic Canada: New data, intercontinental comparisons and correlations - Fletcher, T.L.; Telka, A.; Rybczynski, N.; Matthews, J.V. (Zenodo, 2021)
Fletcher, T.L., Telka, A., Rybczynski, N., Matthews, J.V. (2021): Neogene and early Pleistocene flora from Alaska, USA and Arctic/Subarctic Canada: New data, intercontinental comparisons and correlations. Palaeontologia Electronica (a08) 24 (1): 1-62, DOI:10.26879/1121, URL: http://dx.doi.org/10.26879/1121